Emotional clashes and female public nudity in Thailand. (February 2016) - Thaweesit, Suchada
This article revisits cultural controversies over female public nudity in Thai society. It uses Songkran's topless dancing in 2011 and a bare-breast painting performance on the 'Thailand's Got Talent Show' in 2012 to explore cultural and emotional clashes in Thailand's 21st century. It shows that these two cases of public female nudity drew deep and divergent emotional responses from different groups in Thai society. These cases clearly revealed a clash in viewpoints with regard to Thai notions of feminine respectability associated with national identity and women's sexual expression. On the one hand, the controversies prompted moral panic and backlashes against women's sexual rebelliousness. On the other hand, they set off counter-backlashes against hegemonic discourse that tends to normalise oppressive sexual culture, nationalism and totalitarianism.